Gambaran Kepatuhan Perawat Tentang Surgical Safety Cheklis Dikamar Operasi Rumah Sakit Islam Pemalang - Nurjanah, Siti; Silvitasari, Ika (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Background: Patient safety is important to prioritize in surgical services. Surgical services are services in hospitals that often cause medical injuries and complications that can endanger lives, these incidents can be caused by unintentional events and conditions that result in or have the potential to result in injuries such as Adverse Events, Near Missing Events, Non-Injury Events and Potential Injury Events and sentinel events. Objective: To determine the Description of Nurses' Compliance Regarding the Surgical Safety Checklist in the Operating Room of Pemalang Islamic Hospital. Method: This study is a quantitative study with a descriptive method with 30 respondents using a total sampling technique. Results: Based on the analysis, it was found that in the application of the Surgical Safety Checklist, most respondents were categorized as compliant, namely 19 respondents (63.3%), and 11 respondents (36.7%) were categorized as non-compliant. Conclusion: Compliance with the application of the SSC (Surgical Safety Checklist) was mostly categorized as compliant.